Pengaruh Gaji, Program Pelayanan Dan Kondisi Kerja Terhadap Produktivitas Karyawan (Studi Kasus Pada Karyawan JNE Kota Pasuruan) - Wildan Arif Annafi; Afi Rachmat Slamet; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study 1. To determine the simultaneous effect of salary, service program and working conditions on employee work productivity at JNE Pasuruan 2. To determine and analyze the effect of salary on employee productivity at JNE Pasuruan 3. To determine and analyze the effect of the service program on employee productivity at JNE Pasuruan 4. To find out and analyze the effect of working conditions on employee productivity at JNE Pasuruan. The sample used in this study were 33 respondents. The data analysis method used is quantitative data analysis. To overcome the problem in this study used validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classical assumption test. This study uses multiple linear regression analysis with the help of SPSS 25 program. The results of this study indicate that Salary Statements, Service Programs and Working Conditions have a significant effect on Employee Productivity. Keywords : Salary, Service Program, Working Conditions And Employee Productivity